Clash of sports organization cultures: Differences in table tennis training and coach-athlete relationships between China and Poland - Lenartowicz, M. (International Journal of Sports Science & Coaching, 2023)
This study focused on Chinese-origin table tennis athletes and cross-national comparisons of sports organization cultures with respect to perceived differences in the training process, competition, and coach-athlete relationships between China and Poland. Interviewed Chinese players and Polish coaches reported adaptation problems of Chinese athletes in Poland and numerous differences in table tennis training, organizational culture, and player-coach relations. Chinese athletes were used to a highly disciplined sports environment and formal relationships with coaches. Most of them reported work experiences in Poland as confounding factors in the organization of the training system and the coach-athlete relationships. These relationships were a source of coaching problems, as well as frustration among athletes. Presented cross-national analyses reveal some of the hidden aspects of sports migrations and the impact of cultural differences. The increasing globalization of sports shows that cultural differences should be considered in coaching education, and intercultural competency should be part of coaches` continuous professional development.